Immersed in technology art and virtual environments - Moser, Mary Anne; MacLeod, Douglas (MIT Press, 1996)
Produced as part of the Art and Virtual Environment Project conducted at the Banff Centre for the Arts in Banff, Canada from 1991 to 1994.